Synthesis, structural characterization, and spectroscopic studies of bis-tetraethylammonium hexabromostannate [N(C2H5)4]2SnBr6. (October 2022) - Mhiri, Akram; Krichen, Firas; Oueslati, Abderrazek; Lhoste, Jerome; Hemon-Ribaud, Annie; Gargouri, Mohamed; Bulou, Alain
Abstract: The structure of the new organic–inorganic hybrid compound (TEA)2 SnBr6 (TEA + = tetraethylammonium cation, [N(C2 H5 )4 ] + ), synthesized by slow solvent evaporation at room temperature, has been determined by single-crystal X-ray diffraction analysis. At room temperature, it crystallizes in the trigonal-centrosymmetric space group R -3 c (167) with parameters a = b = 10.7912(2) Å and c = 42.5740(11) Å, as expressed in the corresponding hexagonal cell. The structure of (TEA)2 SnBr6 is built up of isolated SnBr6 octahedra (0D) arranged in a quasi-face-centered system (F). The Raman spectrum of (TEA)2 SnBr6 has been acquired at room temperature in the wavenumber range 10–3600 cm −1 . The results have been analyzed on the basis of group theory (predictions based on space group and compatibility relationships from free SnBr6 2− and TEA + entities), comparison with studies of [N(CH3 )4 ]2 SnBr6, and ab initio calculations on TEA +, and are consistent with the structure. Graphical abstract: The study of the crystal structure of (TEA)2 SnBr6 was determined by X-ray diffraction on a single crystal. Hirshfeld surface analysis employing 3D molecular surface contours and 2D fingerprint plots with enrichment rate calculations were investigated to quantitatively evaluate intermolecular interactions. This compound was additionally characterized using Raman spectroscopy correlated by Ab-initio calculations at different levels of theory. Image 1 Highlights: New organic-inorganic hybrid compound, (TEA)2 SnBr6 was synthesized by slow solvent evaporation at room temperature. The crystal structure was determined by single-crystal X-ray diffraction analysis. The HS and the ER analysis were used for quantifying intermolecular interactions in crystal lattice. Raman spectra is consistent with the structure and ab initio calculations.